Shakespeare’s Culture in Modern Performance - Jones, M. author. aut Link
XII, 213 p. 12 illus.
Keywords: Shakespeare's Culture in Modern Performance is an original study at the interface of a historicizing literary criticism and the study of modern performance. In a critical climate that views the cultural object of performance as authentic in itself, is there any point in exploring a script's original history? The writer argues for a dialogic understanding of Shakespeare's plays in performance relative to unresolved issues of modernity, in a study of modern productions on stage and screen.